Red Beads and Profound Knowledge: Deming and Quality of Education - Sharon Lohr (Arizona State University, 2015)
Value-added models are being implemented in many states in an attempt to measure the contributions of individual teachers and schools toward students' learning. Scores from these models are increasingly used for high-stakes purposes such as setting compensation, hiring or dismissing teachers, awarding tenure, and closing schools. The statistician W. Edwards Deming wrote extensively about improving quality in education and the damage caused by performance rankings. We examine uses and misuses of value-added models in the context of Deming's System of Profound Knowledge, and discuss contributions a Deming-based perspective and statistical science can make to improving education.